1989
DOI: 10.1017/s0140525x00023992
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in human mate preferences: Evolutionary hypotheses tested in 37 cultures

Abstract: Contemporary mate preferences can provide important clues to human reproductive history. Little is known about which characteristics people value in potential mates. Five predictions were made about sex differences in human mate preferences based on evolutionary conceptions of parental investment, sexual selection, human reproductive capacity, and sexual asymmetries regarding certainty of paternity versus maternity. The predictions centered on how each sex valued earning capacity, ambitionindustriousness, yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

189
2,953
26
107

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,780 publications
(3,381 citation statements)
references
References 96 publications
189
2,953
26
107
Order By: Relevance
“…In complex societies, several studies have found that women place greater value on a potential long-term male's education than men do (Buss 1989;Sprecher el al. 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In complex societies, several studies have found that women place greater value on a potential long-term male's education than men do (Buss 1989;Sprecher el al. 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Hadza men probably preferred fatter women because it is important to store energy for pregnancy and lactation and no foraging woman, certainly no Hadza woman, is ever too fat, a fact that may also explain the Hadza preference for a high waist-to-hip ratio (Marlowe and Wetsman 2001). Unlike women in complex societies (Buss 1989;Sprecher et al 1994). Hadza women did not value looks significantly less than men did, though if youth and fertility are considered aspects of appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas sex for males generally does not preclude immediate future reproductive success, sex for females potentially does, given women's nine-month gestation period and subsequent lactation commitment. Also, sexual activities place women at greater risk for sexually transmitted diseases (Varghese, Maher, Peterman, Branson, & Steketee, 2001) and reputational damage than men (Buss, 1989;Dickemann, 1981). Because women paid such higher costs for poor sexual choices across evolutionary history, they should thus be much more avoidant of (and hence more disgusted by) a variety of sexual behaviors.…”
Section: Studymentioning
confidence: 99%
“…These models aim to disentangle the forces hypothesized to be responsible for the origins of the FGMo trait (virginity assurance [Buss 1989] and/or costly signaling [Grafen 1990;Zahavi 1975]) from those that cause its persistence in contemporary populations (frequency dependence [McElreath et al 2008]). Ross et al (2015) contend that the practice of FGMo can be understood as arising from the constraints of marriage markets in much the same way as bridewealth and marriage payments (Anderson 2003;Bell and Song 1994;Borgerhoff Mulder 1995;Chiappori et al 2002).…”
Section: Evolutionary Accounts Of Fgmo Emergence Transmission and Pmentioning
confidence: 99%